HUBUNGAN STATUS GIZI DAN TEKANAN DARAH TERHADAP KADAR HEMOGLOBIN PADA WANITA USIA SUBUR (WUS) DI PONDOK PESANTREN - Pibriyanti, Kartika; Rahmatul Ilmi, Maftuha; Luthfiya, Lulu'; Nabawiyah, Hafidhotun (Jurnal Ilmiah Kebidanan Imelda, 2023)
Hemoglobin (Hb) is a component that plays an important role in the body’s metabolic balance, low Hb called anemia and if it is more than normal it can be called boodhypercoagulation. If not trated immediately the impact will be carried on until the women ismerried, pregnant, and gives birth. The purpose of this study was analyze the relationship between nutritional status and blood pressure to hemoglobin levels of women of childbearing age in Islamic boarding school. This study used a case-control design. The subject of this study age 17-24 years were selected using consecutive sampling. The number of subject was 61 in the case group and 61 in the control group. Data include nutritional status with BMI and MUAC, systolic and diastolic blood pressure. The result of the analysis test showed that there was a significant relationship between nutritional status (BMI) and hemoglobin levels with a p-value 0,025. While nutritional status (MUAC) did nor had a significant relationship with hemoglobin levels, the p-value was 0,328. For systolic and diastolic blood pressure there was also no relationship between the nutritional status of BMI and hemoglobin levels. There was no relationship between blood pressure to hemoglobin levels in women of childbearing age